Intimate Femicide: An Ecological Analysis - Stout, Karen (1992)
This research identifies the killing of women by male partners as a multidimensional problem and, through empirical analysis, identifies relationships between intimate femicide and individual, family, community services, state status of women, and violence against women factors. The conceptual base follows an ecological framework. Individual demographic and situational factors are presented. The findings of the study indicate that factors within each of the ecological settings are associated with intimate femicide. An implication of this exploratory study is that intimate femicide is related to a number of state factors, including factors associated with gender inequality in a state